Analisis Performa Produksi Ayam Broiler Strain Cobb 500 dan Cobb 700 Pada Fase Starter di Kandang Closed House PT DMC Malang - Amrullah, Daniel Taufik; Widodo, Nur; Khasanah, Himmatul; Jadmiko, Mochammad Wildan (Jurnal Peternakan Lingkungan Tropis, 2024)
The success of broiler farming can be seen from the appearance or production performance. One of the factors that can affect production performance is strain. Selection of the right strain can affect the efficiency of broiler production. The purpose of this study was to analyze the production performance of broiler strains Cobb 500 and Cobb 700 in the starter phase at PT Dinamika Megatama Citra. This research was conducted in October 2023 - May 2024. This research was conducted in a broiler farm with a closed house cage system. The location of this research was located in the internal farm of PT Dinamika Megatama Citra, Bocek Village, Karang Ploso District, Malang Regency, East Java. Variables observed in the study include feed intake, body weight gain, feed conversion ratio (FCR), index performance (IP) and mortality. The data obtained in this study will be analyzed using independent t test. The results showed the feed intake of strain Cobb 500 (1221 g/head/3 weeks) was higher than strain Cobb 700 (1209 g/head/3 weeks), body weight gain of strain Cobb 500 (985 g/head/3 weeks) was higher than strain Cobb 700 (938 g/head/3 weeks), FCR strain Cobb 500 (1.20) is lower than strain Cobb 700 (1.24), index performance strain Cobb 500 (389) is higher than strain Cobb 700 (360) while for the death rate or mortality of strain Cobb 500 (4.5%) is not significantly different from strain Cobb 700.